Active Healthy Kids Canada’s Position on Active Video Games for Children and Youth - Chaput, Jean-Philippe (Pulsus Group Inc, 2013)
The effect of active video games (AVGs) on acute energy expenditure has previously been reported; however, the influence of AVGs on other health-related lifestyle indicators remains unclear. To address this knowledge gap, Active Healthy Kids Canada (AHKC) convened an international group of researchers to conduct a systematic review to understand whether AVGs should be promoted to increase physical activity and improve health indicators in children and youth (zero to 17 years of age). The present article outlines the process and outcomes of the development of the AHKC’s position on active video games for children and youth. In light of the available evidence, AHKC does not recommend AVGs as a strategy to help children be more physically active. However, AVGs may exchange some sedentary time for light- to moderate-intensity physical activity, and there may be specific situations in which AVGs provide benefit (eg, motor skill development in special populations and rehabilitation).